The Impact of Augmented Reality on Visual-Spatial Ability Development: Systematic Literature Review - Pratama, Alvonda Rizqi; Efendi, Agus; Sukmawati, Fatma (Universitas Muhammadiyah Surakarta, 2025)
Visual-spatial ability is an essential cognitive skill in supporting learning in science, technology, engineering, and mathematics (STEM). The purpose of this study is to analyze the effect of augmented reality technology on the development of students' visual-spatial abilities through a Systematic Literature Review (SLR) approach. This study is based on 13 relevant articles published in reputable journals for the period 2020–2024. The results of the study show that augmented reality has a significant impact on creating interactive and immersive learning experiences. This technology allows students to visualize complex spatial concepts more easily while increasing motivation and engagement in learning. The use of augmented reality also supports students in understanding spatial-based materials more effectively, making it one of the relevant technological innovations to advance modern education. This study confirms that augmented reality has great potential to improve the quality of visual-spatial-based learning. These findings provide a strong basis for integrating augmented reality into various educational contexts to support the application of technology in innovative and effective learning.